Caregiver Burden and Depression Among Caregivers of Patients with Chronic Disease - Mohamad, Norfidah; Mulud, Zamzaliza Abdul; Tutienande , Nurfeekah Afzatul; Sazaly, Nur Nadhrah; Ibrahim, Nurul Hazirah (Jurnal Ners, 2024)
Introduction: Caring for people with chronic diseases is physically and emotionally demanding. It can also have adverse effects on the caretaker, such as depression. Caregiver burden describes the psychological and financial strains of providing care. Depression in caregivers' manifests as concern, indecision, and an inability to feel the future. Chronic disease is a condition that takes a long time to treat and may progressively get worse over time. This study aims to identify the level of caregiver burden and depression and the correlation between burden and depression among caregivers of patients with chronic diseases. Methods: A self-administered questionnaire containing the Caregiver Burden Inventory and Beck Depression Inventory was used to measure caregiver burden and depression among 217 caregivers of patients with chronic diseases in a teaching hospital in the Klang Valley. Results: The findings showed that the majority of caregivers experienced a mild burden (n = 168, 77.4%), a moderate burden (n = 43, 19.8%), and a severe burden (n = 6, 2.8%). Following mild depression (n = 17, 7.8%), moderate depression (n = 15, 6.9%), and severe depression (n = 4, 1.8%), some caregivers experienced minimal depression (n = 181, 83.4%). According to Pearson's analysis, the link between caregiver burden and depression was statistically significant (p<0.000) with a positive correlation (r = 0.408). Conclusion: In this study, caregivers experienced burden and depression due to providing care. Future studies should incorporate support and resources for caregivers, including respite care and counselling that can promote overall well-being.